2008
DOI: 10.1158/1535-7163.mct-07-2422
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid cancer: targeting the RET kinase pathway with sorafenib/tipifarnib

Abstract: Medullary thyroid carcinoma (MTC) is an uncommon malignancy of hereditary and sporadic presentation. Mutations in the RET proto-oncogene are involved in the pathogenesis of familial MTC and >50% of the sporadic cases. Currently, there is no effective treatment for recurrent or metastatic MTC. We report here a rapid response to a sorafenib (RET and RAF kinase and vascular endothelial growth factor receptor inhibitor) -based regimen in a patient with sporadic MTC who had advanced, progressive disease and a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…The antiproliferative activity of sorafenib varies widely depending on the oncogenic signaling pathways driving proliferation. For tumor cell lines with a single activating oncogenic tyrosine kinase mutation [such as MV4-11 and EOL-1 leukemic cell lines that contain a Flt-3 gene, mutant T670I cKIT that renders patients with gastrointestinal stromal tumor refractory to imatinib (29,30), or oncogenic RET variants (15,31) in metastatic thyroid cancer; ref. 32], the antiproliferative activity of sorafenib is in the low nanomolar concentration range (14,33).…”
Section: Targets For Sorafenibmentioning
confidence: 99%
“…The antiproliferative activity of sorafenib varies widely depending on the oncogenic signaling pathways driving proliferation. For tumor cell lines with a single activating oncogenic tyrosine kinase mutation [such as MV4-11 and EOL-1 leukemic cell lines that contain a Flt-3 gene, mutant T670I cKIT that renders patients with gastrointestinal stromal tumor refractory to imatinib (29,30), or oncogenic RET variants (15,31) in metastatic thyroid cancer; ref. 32], the antiproliferative activity of sorafenib is in the low nanomolar concentration range (14,33).…”
Section: Targets For Sorafenibmentioning
confidence: 99%
“…Although initially developed as an approach to target RAS in cancer, FTI have later been recognized as acting by additional and more complex mechanisms, involving RhoB, centromere-binding proteins and probably other farnesylated proteins. Hong et al (2008) reported on a patient with sporadic MTC with metastatic disease, who was treated with a combination of sorafenib (RET and RAF kinase and vascular endothelial growth factor receptor inhibitor) and tipifarnib (inhibitor of RAS farnesylation), which resulted in a marked clinical response. In a phase I study, it was shown that combining the multikinase inhibitor sorafenib with the FTI tipifarnib resulted in significant activity, particularly in patients with RET mutations (Hong et al 2009).…”
Section: Ras Mutations As a Therapeutic Target In Mtcmentioning
confidence: 99%
“…However, none of these inhibitors are FDA approved on the basis of targeting RET aberrations. Meanwhile, there are a series of reports suggesting that matched therapies against RET aberrations can yield significant responses (8,15,(21)(22)(23)(24)(25)(26)(27). Further clinical trials with a focus on RET-aberrant advanced cancer are being conducted to determine impact on outcome (Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%